A Smartphone App to Facilitate Remote Patient-Provider Communication in Hearing Health Care: Usability and Effect on Hearing Aid Outcomes - Elizabeth Convery; Gitte Keidser; Margot McLelland; J. Groth (2019)
Background:Patients often need multiple fine-tuning appointments with their hearing health care provider to achieve satisfactory hearing aid outcomes. A smartphone app that enables patients to remotely request and receive new hearing aid settings could improve hearing health care access and efficiency.Introduction:We assessed the usability of ReSound Assist™, (ReSound America, Bloomington, MN) the remote communication feature of a hearing aid app, and investigated whether hearing aid outcomes are influenced by app-based versus in-person patient-provider communication.Materials and Methods:Thirty adults were fit bilaterally with hearing aids and randomized to intervention and control groups. During a 6-week field trial, participants reported hearing aid problems via ReSound Assist (intervention) or at a scheduled face-to-face follow-up appointment (control). Usability of ReSound Assist was assessed with a questionnaire and interview. Hearing aid performance, benefit, satisfaction, and daily usage were compared for both groups.Results:ReSound Assist was rated as highly usable. Participants identified specific aspects of effectiveness and efficiency that could be improved. Similar problems were reported by intervention and control participants regardless of communication mode (app-based vs. in-person). However, almost half the requests received via ReSound Assist were for problems that required advice from the provider or physical modifications to the hearing aids rather than fine-tuning, highlighting the continued importance of in-person hearing health care. There was no significant difference in hearing aid outcomes between intervention and control participants.Conclusions:Apps enabling remote patient-provider communication are a viable method for hearing aid users to seek and receive help with hearing aid problems that can be addressed through fine-tuning.